Membangun Good Governance di Lembaga Amil Zakat, Infaq dan Shadaqah (LAZ): Pengalaman Dua LAZ Besar di Indonesia - Ahim Abdurahim; Hafiez Sofyani; Sigit Arie Wibowo (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
This study aims to explore experiences of two big LAZs in Indonesia, namely Lazis Based on Islamic Organization X and Rumah Zakat in complying requirements as a good governance Lazis, with reference to Religion Ministerial Decree (Keputusan Menteri Agama/KMA) 333/2015 about Guidance on Giving Permit Establishment of Amil Zakat Institute and Statement of Financial Accounting Standards (PSAK) No. 109 on Accounting for Zakat and Infak/Alms. Specifically, this study was conducted with interview and observation techniques. Object observations are: Legality, Organizational Structure, Human Resource Quality, Work Program Planning, Implementation Work, Data Management, and Reporting. This study indicate hat there are several points of the requirements that become obstacles, namely: Registered as an Islamic social institution that manages the field of education, da'wah and social or institutional bodies law, Having a planned program plan and trstruktur, Have the technical, administrative and financial skills to carry out its activities, Have state health insurance (BPJS) and employment or other insurance for its employees, and able to raise funds at least 50 billion for LAZNAS. From the various obstacles that arise, the two LAZ has a similar pattern in solving them, namely by adopting the practice of New Public Management for the management and governance of Lazis can run well. In addition, synergy with various parties, such as academics and NGOs, and utilize the progress of information technology by building an e-donation system to optimize the collection of zakat and infaq potentials from various regions in Indonesia. The results of this study are expected to be an input for other LAZ in improving the quality of management and governance, especially related to the filing of legality to the Ministry of Religious Affairs of Indonesia regulated in KMA 333 2015.